Response of Root-Associated Bacterial Communities to Different Degrees of Soft Rot Damage in Amorphophallus konjac Under a Robinia pseudoacacia Plantation - He, Fei (Frontiers in Microbiology, 2021)
Bacterial soft rot is a destructive disease that restricts the development of the konjac (Amorphophallus konjac K. Koch ex N.E.Br) industry. The objective of this study was to investigate how soft rot disease affects root-associated bacterial communities in konjac stands under a pure Robinia pseudoacacia forest. Three konjac stands affected by different degrees of soft rot damage were selected based on their incidence (0%, non-diseased; 4.2%, moderately diseased; and 18.6%, highly diseased). The variation in root-associated bacterial diversity and community composition among the konjac stands was determined by Illumina HiSeq sequencing of the bacterial 16S rRNA genes. The results showed that the contents of soil organic matter and available nutrients (N, P, and K) increased with increasing damage degree, whereas higher damage degree resulted in lower soil pH and enzymatic activity (sucrase, urease, catalase, and polyphenol oxidase). The composition of root-associated bacterial communities differed among the three konjac stands. Proteobacteria was the most dominant bacterial phylum in all rhizosphere soil and root samples. Pseudomonas, Bacillus, Rhizobium, and Streptomyces were most abundant in all samples from the non-diseased konjac stand, whereas Pectobacterium carotovorum subsp. carotovorum and Serratia were predominant in the samples from the moderately and highly diseased stands. The abundance and alpha diversity of root-associated bacteria were significantly higher (P < 0.05) in the non-diseased stand than in the diseased stands. The results suggested pronounced differences in the abundance, alpha diversity, and community composition of root-associated bacteria among the konjac stands affected by different degrees of soft rot damage. Such differences in bacterial communities were related to dynamic changes in soil variables, especially soil available potassium content, sucrase activity, and urease activity. Analysis of the dominant root-associated bacterial taxa offers an approach to predict the damage degree due to soft rot in konjac and provides evidence for the prevention of this soil-borne disease via microecological regulation.